2019
DOI: 10.1128/jvi.00017-19
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramidase Maintains Influenza Virus Infection by Regulating Endocytosis

Abstract: Influenza virus is an RNA virus encapsulated in a lipid bilayer derived from the host cell plasma membrane. Previous studies showed that influenza virus infection depends on cellular lipids, including the sphingolipids sphingomyelin and sphingosine. Here we examined the role of a third sphingolipid, glucosylceramide, in influenza virus infection following clustered regularly interspaced short palindromic repeats with Cas9 (CRISPR-Cas9)-mediated knockout (KO) of its metabolizing enzyme glucosylceramidase (GBA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 73 publications
2
32
0
Order By: Relevance
“…Previously, we found that deleting GBA1, the enzyme that converts GlcCer (the primary product of UGCG enzymatic activity) to ceramide (Fig 1) increases GlcCer levels and impairs endosome trafficking and influenza virus entry [25]. Here we found that knocking out UGCG decreases GlcCer levels (in both HEK 293 and A549 cells), impairing the entry of endosomeentering viruses.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Previously, we found that deleting GBA1, the enzyme that converts GlcCer (the primary product of UGCG enzymatic activity) to ceramide (Fig 1) increases GlcCer levels and impairs endosome trafficking and influenza virus entry [25]. Here we found that knocking out UGCG decreases GlcCer levels (in both HEK 293 and A549 cells), impairing the entry of endosomeentering viruses.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies demonstrated that loss of expression or inhibition of several sphingolipidmetabolizing enzymes leads to reduced influenza virus infection (Fig 1). We recently discovered that glucosylceramidase (GBA) is required for optimal influenza virus entry [25]. We thus hypothesized that glucosylceramide synthase (UGCG), which converts ceramide to glucosylceramide, may also play a role in the influenza virus life cycle (green box).…”
Section: Glucosylceramide Synthase Regulates Influenza Virus Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human Cytomegalovirus (HCMV) induces elevation of ceramide and GM2-ganglioside (10), and Dengue virus induces elevation of ceramide and sphingomyelin (11). Additionally, Influenza virus was shown to induce Sphingomyelin and GlcCer elevation (12,13) and suppression of the biosynthesis of cellular sphingolipids results in the inhibition of the maturation of influenza virus particles in vitro (14,15). Moreover, iminosugars are known for their broad-spectrum antiviral activity, presumably because of their mechanism of action as endoplasmic reticulum (ER)-resident α-glucosidases I and II inhibitors (16).…”
Section: Introductionmentioning
confidence: 99%